Peripheral ossifying fibroma - Vaishali Keluskar; Raghavendra Byakodi; Nishit Shah (Wolters Kluwer Medknow Publications, 2008)
Here we report an unusual case of peripheral ossifying fibroma in a 57-year-old woman, who reported to the KLES Institute of Dental Sciences, Belgaum. Clinically, the lesion appeared as a nodular swelling on the gingiva. Though the possibility exists that the lesion is reactive, it appears to be true neoplastic growth and a purely soft tissue process arising from the gingiva. Thus, we proposed the term peripheral ossifying fibroma for this distinct lesion.